2022
DOI: 10.5334/ijc.1143
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Biodiversity Conservation in Sacred Groves: A Comparative Study of Three Sacred Groves in Southwest Nigeria

Abstract: Globally, sacred groves represent a traditional form of community-based conservation, recognized as areas of cultural and religious importance to local people. In some cases, the entire community guards against the desecration of, or unauthorized access to, such sites, either by its members or outsiders; in others, non-recognition of customary rights is linked to degradation. This paper uses the case study of three sacred groves in southwest Nigeria to examine the extent to which perceived socio-economic and r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Religious beliefs and taboos were central to the protection of sacred groves in India, which led to increase in tree species diversity (Khan et al 2008, Sundarapandian & Subbiah 2015. The good conservation status of most sacred groves in this study is attributed to the fact that indigenous communities consider the groves as the home of deities, place of worship and cultural site and festivals, and consequently refrained from destroying them, which is similar to the situation in Tanzania (Adeyanju 2020, Onyekwelu 2021, Mgumia & Oba 2003. In a previous study, Onyekwelu and Olusola (2014) attributed the low species diversity in Igbo-Olodumare grove to its "low sacredness" since only 5% of community dwellers consider the grove as the home of deity and place of worship, which may have led to encroachments.…”
Section: Biodiversity Indices and Conservation Status Of The Sacred G...supporting
confidence: 60%
See 3 more Smart Citations
“…Religious beliefs and taboos were central to the protection of sacred groves in India, which led to increase in tree species diversity (Khan et al 2008, Sundarapandian & Subbiah 2015. The good conservation status of most sacred groves in this study is attributed to the fact that indigenous communities consider the groves as the home of deities, place of worship and cultural site and festivals, and consequently refrained from destroying them, which is similar to the situation in Tanzania (Adeyanju 2020, Onyekwelu 2021, Mgumia & Oba 2003. In a previous study, Onyekwelu and Olusola (2014) attributed the low species diversity in Igbo-Olodumare grove to its "low sacredness" since only 5% of community dwellers consider the grove as the home of deity and place of worship, which may have led to encroachments.…”
Section: Biodiversity Indices and Conservation Status Of The Sacred G...supporting
confidence: 60%
“…Khan et al (2008) reported large sacred groves of up to 26,326 ha. Encroachment was observed to be minimal in the sacred groves, which can be attributed to the effectiveness of the taboos, local laws, customs and regulations used in their management, in addition to the prohibition or highly regulated access (Borokini 2016, Adeyanju 2020. Due to respect and fear of the taboos and deities, people usually keep away from the sacred groves, and thus refrain from felling trees within the site (Onyekwelu & Olusola 2014).…”
Section: Growth Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sacred forests are the remnant surviving forest patches that preserve indigenous and old-growth forest trees with cultural and/or religious importance to the local people [ 5 , 6 ]. Sacred forests are found in many countries all over the world and are particularly common in parts of Asia and Africa [ 7 ]. Sacred forests are playing a significant role in biodiversity conservation and combating climate change [ 8 ] since exploitation is relatively prohibited due to spiritual and cultural taboos and rules and customs.…”
Section: Introductionmentioning
confidence: 99%